1995
DOI: 10.1056/nejm199504273321702
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Evidence of Graft Survival and Striatal Reinnervation after the Transplantation of Fetal Mesencephalic Tissue in a Patient with Parkinson's Disease

Abstract: Grafts of fetal mesencephalic tissue can survive for a long period in the human brain and restore dopaminergic innervation to the striatum in patients with Parkinson's disease. In the patient we studied, clinical improvement and enhanced fluorodopa with uptake on PET scanning were associated the survival of the grafts and dopaminergic reinnervation of the striatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
408
2
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 808 publications
(430 citation statements)
references
References 29 publications
13
408
2
5
Order By: Relevance
“…Freed et al [6] demonstrated 18% reduction in Unified Parkinson's Disease Rating Scale motor score compared to the sham group score at 12 months after bilateral intraputaminal grafts. Two patients who died only had between 7,000 and 40,000 grafted dopaminergic neurons in each putamen [6], which were much fewer than were found in 2 patients in an open-label trial (i.e., between 80,000 and135,000 [22][23][24]). This may be due to having less tissue implants, or storage in cell culture for as much as 4 weeks, or lack of immunosuppression.…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 78%
See 1 more Smart Citation
“…Freed et al [6] demonstrated 18% reduction in Unified Parkinson's Disease Rating Scale motor score compared to the sham group score at 12 months after bilateral intraputaminal grafts. Two patients who died only had between 7,000 and 40,000 grafted dopaminergic neurons in each putamen [6], which were much fewer than were found in 2 patients in an open-label trial (i.e., between 80,000 and135,000 [22][23][24]). This may be due to having less tissue implants, or storage in cell culture for as much as 4 weeks, or lack of immunosuppression.…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 78%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…But after longer incubation periods (12-16 years), α-synuclein and ubiqutin-positive Lewy body pathology was identified in the fetal grafts [25,26]. The presence of metabolically and phenotypically normal dopaminergic grafts early in this process (18 months) suggested a long lag phase before induction of pathology [27][28][29]. Several hypotheses were presented to explain the spread of pathology into these young neurons, including the possibility that neuron-to-neuron spread of α-synuclein induced further aggregation in the fetal grafts.…”
Section: Spread Of α-Synuclein Pathology To Young Neurons In Human Pamentioning
confidence: 99%
“…Kordower et al [42], who did bilateral transplants of fragments of embryonic mesencephalon into postcommissural putamen, were the first to demonstrate surviving dopamine cells postmortem. The patient was immunosuppressed with cyclosporine for 6 months and died 18 months after transplant.…”
Section: Postmortem Survival Of Human Fetal Dopamine Neuronsmentioning
confidence: 99%
“…Unfortunately, approximately 95% of dopamine neurons die after transplantation of rat or human tissue. In human patients, no more than 20,000 to 25,000 dopamine cells survive from each embryo transplanted [7,42]. Some investigators have argued that such a high rate of cell death requires that tissue from 6 or more donors be transplanted into each putamen to restore a complete complement of dopamine-producing neurons.…”
Section: Number Of Donors -Tissue From 4 Donors Provides Sufficient Dmentioning
confidence: 99%